Testing the Kerr hypothesis using x-ray reflection spectroscopy with NuSTAR data of Cygnus X-1 in the soft state - Liu, Honghui; Abdikamalov, Askar B.; Ayzenberg, Dimity; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Nampalliwar, Sourabh (Physical Review D, 2019)
We continue exploring the constraining capabilities of x-ray reflection spectroscopy to test the Kerr-nature of astrophysical black holes, and we present the results of our analysis of two NuSTAR observations of Cygnus X-1 in the soft state. We find that the final measurement can strongly depend on the assumption of the intensity profile. We conclude that Cygnus X-1 is not suitable for tests of general relativity using x-ray reflection spectroscopy, and we discuss the desired properties of a source to be a good candidate for our studies.
CRIS-Team WoS Importer:2019-07-02